Antibacterial Studies of 3,5-Diaryl-1-4-Benzoyl-1-Pyridoyl Pyrazoles - Kadu, M.V.; Jamode, V.S. (Asian Journal of Chemistry, 2010)
3,5-Diaryl-4-benzoyl-1-pyridoyl pyrazoles (4a-j) had been synthesized from 3-aroyl flavones and isoniazide in pyridine medium. structures of these compounds have been confirmed by spectral analysis. These compounds were tested for their antibacterial activities against pathogenic bacteria and are found to have moderate activity.